Wybrane uwarunkowania procesu zarządzania bankami spółdzielczymi na tle przekształceń polskiego systemu bankowego - Magdoń, Antoni (Przegląd Prawno-Ekonomiczny, 2008)
Streszczenie dostępne wyłącznie w języku angielskim: Transformation of the polish cooperative banks system is connected with reconstruction of bank system in our country. It is related to some kind of risks, but their identification allows to avoid some mistakes, which especially concerns credit policy and irregular loans. On the base of analysis of credit activity, there were separated some essential formal faults which caused the existing bad situation in the credit portfolio in many cooperative banks. The process of cooperative banks recovery is strongly connected with bank’s consolidations. There are two ways of consolidations, first there is connection of existing banks and second one bank takes over assets of bank which is liquidated. In the process of the reform of system we must to remember about the role and importance of the local bank and their members, who always decided about strength and condition of local bank.